Mechanical behavior of polylactic acid/polycaprolactone porous layered functional composites. (1st August 2016) - Scaffaro, Roberto; Lopresti, Francesco; Botta, Luigi; Maio, Andrea
Abstract: Biopolymeric porous devices exhibiting graded properties can play a crucial role in several fields, such as tissue engineering or controlled drugs release. In this context, the gradient of a specific property can be achieved by developing porous laminates composed by different types of materials. This work presents for the first time a multi-phasic porous laminate based on polycaprolactone (PCL) and polylactic acid (PLA) prepared by combining melt mixing, compression molding and particle leaching. All the materials were characterized from a morphological and a mechanical point of view. The results put into evidence the possibility to tune and to predict the mechanical properties by controlling the process parameters together with geometrical features.